STUDENTS PERCEPTION OF USING GOOGLE CLASSROOM AS ENGLISH TEACHING MEDIA DURING CORONA VIRUS 2019 AT SMA NEGERI 4 PEMATANGSIANTAR - Renta Silalahi; Dumaris E. Silalahi; Herman . (STKIP PGRI Jombang, 2021)
Since March 2020, teaching and learning at schools have come to a new reality that both teachers and students should be able utilize any model of online learning due to the outbreak of Corona Virus Disease (Covid-19). Google Classroom is a online learning platform has been considered the possible approach to continue the teaching and learning process during this pandemic. Referring to this case, this research was intended to find out students perception of using Google Classroom as English teaching media during Corona Virus 2019. The implementation was observed engaging 34 students of 11-PMIA-2. Survey research was used to find out students perception of using Google Classroom in online English class. Questionnaire was used to collect the data about students’ perception. The results showed students have positive perception toward Google Classroom. It was online teaching media which able to support students English learning activities and made students engaging in learning English,useful and helpful for the students in order to achieved English learning goal by using the system distributed ,managing-grading task,teacher intervention on feedback and evaluation task of students which helped students learnt and understand English during Corona Virus 2019.